TRADISI MIPIT PARE DALAM BINGKAI LIVING QUR'AN DI PANDEGLANG BANTEN - Maharani, Nina (Al-Fath, 2022)
Humans are encouraged to strive to get something, namely by trying and praying as much as possible, as well as the people of Kacapi Kutamekar Village, making the mipit pare tradition as part of the efforts and prayers that are made to achieve the expected harvest and as a sign of gratitude to God for rice planting success. The mipit pare tradition is carried out before the harvest, by reading selected verses and praying Nurbuat. This tradition is carried out with the aim that the harvest is protected from all kinds of bad things, asks Allah to bless the harvest, and as a sign of gratitude because Allah has given sustenance to the farmers by growing their rice so that their rice can be harvested. This thesis tries to see and analyze the phenomena carried out by the people of Kampung Kacapi who make the mipit pare tradition a form of prayer and gratitude to Allah. The author uses the Living Qur'an research method, namely scientific research on various social events related to the presence of the Qur'an in certain Muslim communities. The approach used by the author is a phenomenological approach.